Corporate governance and risk management: An evaluation of board responsibilities in western and Islamic banks - Alatassi, Bchr; Pillai, Rekha (Economics and Business Review, 2024)
This research aims to explore the role of the board in cor-porate governance (CG) and risk management within the context of Islamic banking. Given the global reach of fi-nancial institutions, it is important to compare and evalu-ate the unique position of Shari’ah committees or Shari’ah Supervisory Board (SSB) in addressing the unique risks of Islamic banks. Using a comparative analysis, this study evaluated risk management guidelines in the CG codes of the United Kingdom, Germany, Saudi Arabia, and Malaysia. It found that board were ultimately responsible for risk management, regardless of the governance structure, and Shari’ah-related risks fell under the board’s purview. An innovative blend of Western CG frameworks and Islamic principles enhanced governance robustness through the strategic collaboration between board and SSBs.